2013
DOI: 10.1001/jamaoto.2013.5189
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Surgery for Primary Head and Neck Squamous Cell Carcinoma of Unknown Site

Abstract: We demonstrate that TORS is a useful approach to identify and treat the primary site in patients with HNSCC who present with an unknown primary site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 39 publications
3
84
0
2
Order By: Relevance
“…Some recent studies suggest that transoral laser microsurgery (TLM) or transoral robotic surgery (TORS) is more effective for the identification of a primary in the oropharynx especially in the base of tongue (BOT) in patients with suspected CUP [37,38]. Recent case series have reported high rates of detection ranging from 86 to 94% including TLM [38,39] and 72 to 90% including TORS [37,38,40] in the diagnostic work-up of patients with suspected CUP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some recent studies suggest that transoral laser microsurgery (TLM) or transoral robotic surgery (TORS) is more effective for the identification of a primary in the oropharynx especially in the base of tongue (BOT) in patients with suspected CUP [37,38]. Recent case series have reported high rates of detection ranging from 86 to 94% including TLM [38,39] and 72 to 90% including TORS [37,38,40] in the diagnostic work-up of patients with suspected CUP.…”
Section: Discussionmentioning
confidence: 99%
“…Recent case series have reported high rates of detection ranging from 86 to 94% including TLM [38,39] and 72 to 90% including TORS [37,38,40] in the diagnostic work-up of patients with suspected CUP. According to Durmus et al [41] the PT was identified in 77% of patients (17 of 22) with 80% HPV-positive LNM residing in the palatine tonsil in 59% (13 of 22), and the BOT in 18% (4 of 22).…”
Section: Discussionmentioning
confidence: 99%
“…Literatür bilgisi ışığında PBM' da primer lezyonu bulmak için transervikal USG ile hipoekoik lezyon aranmasının yararlı olabileceği söylenebilir (18). Literatürde PET-BT'de primer lezyon gösterilememiş ve transoral robotik cerrahi (TORS) ile lingual tonsillektomi yapılarak dil kökünde primer odağın saptandığı yayınlar mevcuttur (19)(20)(21). TORS ile lingual tonsillektomi PBM'da yeni bir uygulamadır ve primer lezyonu saptamada faydalı olarak görülmektedir (19)(20)(21).…”
Section: Lap Lokalizasyonu Ile Primer Lezyonun İlişkisiunclassified
“…Literatürde PET-BT'de primer lezyon gösterilememiş ve transoral robotik cerrahi (TORS) ile lingual tonsillektomi yapılarak dil kökünde primer odağın saptandığı yayınlar mevcuttur (19)(20)(21). TORS ile lingual tonsillektomi PBM'da yeni bir uygulamadır ve primer lezyonu saptamada faydalı olarak görülmektedir (19)(20)(21). Primer lezyonu saptamak için immünohistokimyasal ve moleküler çalışmalar yapılabilir.…”
Section: Lap Lokalizasyonu Ile Primer Lezyonun İlişkisiunclassified
“…TORS is currently being used in the management of early-stage tumors, more advanced malignancies, tumor recurrences, deep neck space infections, tumors of unknown primary site, and comparatively benign conditions such as obstructive sleep apnea [1,[15][16][17][18]. The incidence of postoperative complications seen with TORS is generally low and has the potential to be further reduced by increased experience with the technique and an appreciation of risk factors for the most common issues [5,[19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%